Evaluating the Effectiveness of Indonesia-Germany G to G Labor Placement Agreements: Case Study of Indonesian Nurses in Germany - Stefani Putri Kinanti; Pramana, Lintang Atha Zahfirah (Universitas Muhammadiyah Kotabumi, 2024)
The study titled